Analisis Konglomerasi Industri Pers Daerah di Indonesia: Pendekatan S-C-P - Iwan Awaluddin Yusuf (Jurnal Komunikasi, 2008)
The Structure, Conduct, and Performance or known as S-C-P usually used to observe the structures and competitions in industry, including mass media. Mass media structure, with its centralistic-concentrated ownership as the indication of conglomeration in Indonesian local press competition, practically influences the behavior of media companies. This article deal with the conglomeration in Indonesian local press, since they have to fight in a tough national press competition whose ownerships are concentrated in some publishing groups. The analysis that used to capture local press conglomeration in the oligopoly market is the Structure-Conduct-Performance approach.